Concurrent Village Head Election (Pilkades) Disputes (Analysis of Handling Pattern and Dispute Resolution Process in Tapos, Talagasari, and Dukuh Villages of Tangerang Regency) - Kartika, Ray Septianis (Research and Development Agency Ministry of Home Affairs, 2016)
The appointment of a village head often causes turmoil in some regions. Ranging from internal problem to the resolution through legal channels. This study aims to assess the extent of the Pilkades disputes in Tapos, Talagasari, and Dukuh Villages in Tangerang Regency. By using qualitative analytical descriptive method, the results of this study are (1) the absence of Pilkades dispute resolution medium at the regency, district and village levels, (2) by regulation, PP No 72 of 2005 does not explain the categorization of violations and sanctions against offenders, (3) There is an implied term campaign ends, as amended, Regulation 7 of 2006 article 54, paragraph 8, (4) lack of traction on the role of Head in controlling and supervising corresponding PP No 72 of 2005 and Regulation 7 of 2006, (5) the lack of an audit role, (6) the absence of a competent team of investigators administration. Suggestions that we can recommend is (1) to make the legislation or local regulations that elevate one article about the elections and dispute resolution, (2) Effectiveness muspika role in the elections and, (3) promoting Pilkades order.